ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN PADA PERUSAHAAN PERTAMBANGAN NON MIGAS - tumewu, james; Murni, Siti Asiah; Ika Aprilia, Siti Aiza (Prodi Akuntansi FEB UNITOMO, 2021)
The annual report serves as the main media in the delivery of information by the management of a company to the interested parties outside the company. The purpose of this study was to analyze the effect of firm size, leverage, liquidity, age listed and size of the public accounting firm of the voluntary disclosure on non-oil sector of the mining company listed on the Indonesia Stock Exchange (BEI). Samples were taken using purposive sampling method. There are 60 observations annual financial statements of non-oil mining company. Data analysis technique used is multiple linear regression analysis using.. The results showed that together the size of the company, leverage, liquidity, age listed and size of the public accounting firm influence on voluntary disclosure. Firm size and age listed has a positive effect on voluntary disclosure, but size of public accounting firms has aÂ negative effect on voluntary disclosure, while leverage and liquidity does not effect onÂ voluntary disclosure.